Is a Consensus Case Definition for Viral Associated Lower Respiratory Tract Disease (LRTD) in Clinical Trials Possible? - S. Elizabeth Williams; Bradford Gessner; Elizabeth Begier; Negar Aliabadi; Kumar Ilangovan; Luis Jodar; Cassandra Hall-Murray; Giovanni Checcucci Lisi; Edward Walsh (Infectious Diseases and Therapy)
Abstract Lower respiratory tract illness or disease (LRTI/LRTD) represents a significant source of morbidity and mortality following viral respiratory illnesses, yet a consensus definition for this outcome is lacking. Recent studies of novel vaccines against respiratory syncytial virus (RSV) for older adults used LRTI/LRTD as the primary outcome to assess vaccine efficacy. However, the different vaccine trials have used highly variable criteria to define this outcome, leading to difficulty in comparison of vaccine efficacy results between trials. Here we review the key differences in criteria for case definitions, highlight strategies to best approximate compatibility between definitions, and review vaccine efficacy results among currently US Food and Drug Administration (FDA)-approved vaccines using these strategies. We hope this overview will support the need to develop a consensus definition for LRTI/LRTD to improve future research related to viral respiratory disease.